Respostas

2014-03-13T20:14:40-03:00
A2 = a1 + r
a6 = a1 +5r => (a1 + r) + (a1 + 5r) = -6 => 2a1 + 6r = -6 (/2) => a1 + 3r = -3

a5 = a1 + 4r
a8 = a1 +7r => (a1 + 4r) + (a1 + 7r) = 9 => 2a1 + 11r = 9

a1 + 3r = -3   x (-2) => -2a1 - 6r = 6
2a1 + 11r = 9              2a1 + 11r = 9
                                            5r = 15 => r = 3 => a1 + 3(3) = -3 =>
                                                                    => a1 = -3-9 => a1 = -12
A melhor resposta!
2014-03-13T20:34:54-03:00
A2+a6=-6
a5+a8=9

a6=a1+5r
a5=a1+4r
a8=a1+7r
r=a2-a1, a2=r+a1
trocando os valores de a2, a6,a5 e a8

r+a1+a1+5r=-6
a1+4r+a1+7r=9
somando os semelhantes
2a1+6r=-6 multiplicando por -1
2a1+11r=9

-2a1-6r=6
2a1+11r=9
Somando os termos semelhantes
5r=15
r=15/5
r=3
2a1+6r=-6
2a1+6*3=-6
2a1+18=-6
2a1= -6-18
2a1= -24
a1= -24/2
a1= -12


1 5 1